Desconstrução espacial e produção da área central na cidade de São Paulo : o exemplo da Rua Paim, Bela Vista - Ruivo, Maria Patrícia (2015)
The data released by 2010 Census (IBGE) demonstrated a reversal in the migratory flux in the central area of São Paulo-SP. After decades of decrease in population, neglect and lack of investments, the center of the city started to gain new inhabitants in the first decade of the XXI century. The purpose of this study is to analyze these changes and investigate the production of urban space in the central area of São Paulo between the years 2000 and 2010. Through the case study of Paim Street (Bela Vista), the research intends to discuss this production, not only as a result of the guidelines defined by the city Master Plan, but also as a reaction of real estate market. Despite the legal advances, with the approval of federal Law 10.257 in 2001, the Strategic Master Plan in 2002, and the positive aspects of the population growth in the central area, the investigation indicates that the difficulties to bring about a paradigm shift in the production of urban space in the city still remain. The data show the fail in application of the main urban instruments intended to guarantee the social function of property and the difficulty in protecting the built environment, prioritizing the recovery of old buildings before encouraging the construction of new ones. The importance in understanding the period of study is the possibility to prevent and correct such distortions between theory and what is actually done in the city.